Amon (אמון) in Prov 8:30: A Linguistic, Comparative, and Historical Approach - Anthonioz, Stéphanie (Antiguo Oriente, 2023)
The understanding of Amon (אמון) in the context of the praise of Wisdom personified (Prov 8:30) has been a crux for biblical scholarship from the earliest witnesses on. Modern scholarship has often proposed to emend the Hebrew text and each solution with its own vocalization has produced stimulating contextual or comparative explanations. The aim of this communication is to review the actual state of the question and propose that the solution to this crux is enlightened by these comparative approaches not only from the Mesopotamian point of view but also from the Egyptian one. This analysis will enable us to consider the historical and scribal practices at the heart of this crux so that no exclusive reading is the right solution but rather an inclusive reading leading to a particular understanding of the divine. This case will also point to the reflections and strategies of a religious writing or scribal community in the last centuries before the common era and how the theologian scribes made use of writing as non-vocalized signs to probe and tend to grasp or reveal divine mystery.